2016
DOI: 10.1519/jsc.0000000000001429
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Injury Among Japanese Collegiate Players of American Football Based on Performance Test Results

Abstract: Iguchi, J, Watanabe, Y, Kimura, M, Fujisawa, Y, Hojo, T, Yuasa, Y, Higashi, S, and Kuzuhara, K. Risk factors for injury among Japanese collegiate players of American football based on performance test results. J Strength Cond Res 30(12): 3405-3411, 2016-The purpose of this study was to identify how risk factors for injury during American football are related to players' physical strength as determined using typical performance tests. One hundred 53 Japanese collegiate players of American football were recruite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 33 publications
0
14
0
1
Order By: Relevance
“…The method of the multidimensional analysis is also used in other kinds of physical training and sport: for network analysis of competitive sports [33,34]; forecasting of player's success [35] and forecast of the maximum HR at children and teenagers [36]; forecasting of injuries at athletes in track and field events [37], American soccer [38], snowboard [39].…”
Section: Pedagogics Psychologymentioning
confidence: 99%
“…The method of the multidimensional analysis is also used in other kinds of physical training and sport: for network analysis of competitive sports [33,34]; forecasting of player's success [35] and forecast of the maximum HR at children and teenagers [36]; forecasting of injuries at athletes in track and field events [37], American soccer [38], snowboard [39].…”
Section: Pedagogics Psychologymentioning
confidence: 99%
“…In an American football game, each position has distinct performance demands. Furthermore, previous studies have reported that height, body weight, and body composition are different among American football players (Dupler, Amonette, Coleman, Hoffman, & Wenzel, 2010;Iguchi et al, 2016), and the different speed and movement demands required may be explained by the specific characteristics of each playing position (Robbins & Young, 2012;Raymundo et al, 2018). High-level teams present at least 20 distinct positions.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, wide receivers and defensive backs, who often weigh < 90 kg, are usually required to run distances in excess of 30 or 40 m. Linemen commonly weighing over 140 kg are rarely required to run > 10 m (Robbins & Young, 2012;Iguchi et al, 2016). Players in skill position achieve greater distances, highintensity sprint, and acceleration and deceleration efforts than those in other positions (Nuzzo, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations